The Stock of Intangible Capital in Canada : Evidence from the Aggregate Value of Securities - Belhocine, Nazim (IMF Working Papers; Working Paper ;, 2009)
This paper measures the size of the stock of intangible capital in Canada using newly released data on the market value of all securities in the economy. The approach taken relies on a quantitative application of the q-theory of investment to generate the quantity of capital owned by firms. I find that the intangible capital stock accounted for approximately 30% of overall capital since 1994. Of this intangible capital stock, the R and D reported by national accounts makes up only 23%. In addition, the finding on the magnitude of the intangible capital stock is comparable to that reported using a cost approach, confirming the size and the relevance of intangibles to macroeconomic models.